Application of Internet of things in agriculture products supply chain management - Zhongwei Zhou; Zhongyi Zhou (2012 International Conference on Control Engineering and Communication Technology, 2012)
In recent years, frequent occurring of food quality and safety issues endangered the people's health and the building of harmonious society. Thus, improving the quality and safety of agricultural products, which is of crucial importance to accelerate the change of agricultural increasing method and ensure the safe of urban and rural residents' consumption. This article through the analysis of the construction and integration of the Internet, Internet of things and agricultural products logistics information net to built the new management model, so as to realize the visualization and traceability of agriculture products quality, and ensure people's food safety, and promote the sustainable development of modern agriculture.